The dual role of CD6 as a therapeutic target in cancer and autoimmune disease - Gurrea-Rubio, Mikel; Fox, David A. (Frontiers in Medicine, 2022)
Autoimmune disease involves loss of tolerance to self-antigen, while progression of cancer reflects insufficient recognition and response of the immune system to malignant cells. Patients with immune compromised conditions tend to be more susceptible to cancer development. On the other hand, cancer treatments, especially checkpoint inhibitor therapies, can induce severe autoimmune syndromes. There is recent evidence that autoimmunity and cancer share molecular targets and pathways that may be dysregulated in both types of diseases. Therefore, there has been an increased focus on understanding these biological pathways that link cancer and its treatment with the appearance of autoimmunity. In this review, we hope to consolidate our understanding of current and emerging molecular targets used to treat both cancer and autoimmunity, with a special focus on Cluster of Differentiation (CD) 6.